2014
DOI: 10.1042/bj20131433
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial–nuclear genome interactions in non-alcoholic fatty liver disease in mice

Abstract: Nonalcoholic fatty liver disease (NAFLD) involves significant changes in liver metabolism characterized by oxidative stress, lipid accumulation, and fibrogenesis. Mitochondrial dysfunction and bioenergetic defects also contribute to NAFLD. Herein, we examined whether differences in mtDNA influence NAFLD. To determine the role of mitochondrial and nuclear genomes in NAFLD, Mitochondrial-Nuclear eXchange (MNX) mice were fed an atherogenic diet. MNX mice have mtDNA from C57BL/6J mice on a C3H/HeN nuclear backgrou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 44 publications
1
33
0
Order By: Relevance
“…Yet detailed studies of retinoid signaling in models of NAFLD have not been conducted. Because NAFLD is at least in part a mitochondrial disease associated with decreased mitochondrial gene expression and function (Pessayre, 2007;Wei et al, 2008;Aharoni-Simon et al, 2011;Betancourt et al, 2014), regulation of mitochondrial fatty acid oxidation and lipid homeostasis by atRA could play a role in NAFLD progression. The aim of this study was to determine whether atRA regulates mitochondrial function and lipid homeostasis in the healthy and fatty human liver and to establish how well mouse and rat models of atRA signaling in the liver correlate with models of human liver.…”
Section: Introductionmentioning
confidence: 99%
“…Yet detailed studies of retinoid signaling in models of NAFLD have not been conducted. Because NAFLD is at least in part a mitochondrial disease associated with decreased mitochondrial gene expression and function (Pessayre, 2007;Wei et al, 2008;Aharoni-Simon et al, 2011;Betancourt et al, 2014), regulation of mitochondrial fatty acid oxidation and lipid homeostasis by atRA could play a role in NAFLD progression. The aim of this study was to determine whether atRA regulates mitochondrial function and lipid homeostasis in the healthy and fatty human liver and to establish how well mouse and rat models of atRA signaling in the liver correlate with models of human liver.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous epidemiologic studies have demonstrated that associations exist between mitochondrial haplogroup and the incidence of disease 79, 4749 , and more recent studies in animals have shown that mtDNA background can play a significant role in aspects of disease susceptibility in heart and liver 18, 19 . Whether differences exist in cellular bioenergetics and mitochondrial damage between normal individuals having different mtDNA backgrounds has not been studied in primary cells.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular mechanisms behind these effects are currently unclear; it is unlikely however, that a singular molecular pathway will be the basis due to the nature of mitochondrial metabolism which is at the hub of all cellular metabolism and therefore even subtle changes have the potential for impacting multiple aspects of cellular function. Studies using animal models that examine the impact of different “normal” mtDNA backgrounds have shown effects upon adaptive immunity, cognition, heart failure susceptibility, fatty liver disease, and most recently cancer 13, 18, 19, 70, 71 . The diversity of these phenotypes suggests that a single mechanism is unlikely and instead argues that a complex interaction of mitochondrial and nuclear genetic backgrounds guides cellular metabolism in response to environmental cues and challenges which influences cellular function in response.…”
Section: Discussionmentioning
confidence: 99%
“…Interpopulation hybrids of the marine copepod Tigriopus suffered compromised oxidative phosphorylation (OXPHOS) capacities Burton 2006, 2008b) The importance of mt-n epistasis extends well past arthropods. In mice, mt-n epistasis is known to affect cognition (Roubertoux et al 2003), ROS (Fetterman et al 2013), and respiratory functions (Betancourt et al 2014) as well as tissuespecific selection for mtDNA variants (Jenuth et al 1997). Interactions between mt and n genomes likely contribute to cytoplasmic male sterility in plants (Hu et al 2014) and disease presentation and aging in humans (Tranah 2011;Wallace and Chalkia 2013;Wolff et al 2014), suggesting that mt-n epistasis is important in most eukaryotes.…”
mentioning
confidence: 99%